Предмет: Математика,
автор: Аноним
1) 3(х – 2) = х + 2
2) 3,4 + 2х = 7(х – 2,3)
Ответы
Автор ответа:
0
Ответ:
3х-6=х+2
2х=8
Х=4
3,4+2х=7х-16,1
19,5=5х
3,9=х
Автор ответа:
0
Ответ:
1)
Пошаговое объяснение:
1) 3х-6= х+2
3х-х= 2-6
2х= -4
х=-4/2
х= -2
2) 3,4 +2х= 7х-16,1
2х-7х= -16,1 -3,4
-5х= -19,5
х= 3,9
Похожие вопросы
Предмет: Русский язык,
автор: Kristi1563
Предмет: Окружающий мир,
автор: vredniy83
Предмет: Русский язык,
автор: Аноним
Предмет: Русский язык,
автор: Бенди6987
Предмет: Русский язык,
автор: pavelisiev